Owen & Mzee : the language of friendship - Hatkoff, Isabella; Hatkoff, Craig; Kahumbu, P. (Paula); Greste, Peter (New York : Scholastic Press, 2007)
1. Hippopotamus--Behavior--Kenya--Juvenile literature 2. Aldabra tortoise--Behavior--Kenya--Juvenile literature
Sequel to: Owen and Mzee.
Includes bibliographical references and index.
Basic ed. students
Keywords: Hippopotamus -- Behavior -- Kenya -- Juvenile literature; Aldabra tortoise -- Behavior -- Kenya -- Juvenile literature; Social behavior in animals -- Kenya -- Juvenile literature